Effects of cesarean section on mean platelet volume. (3rd October 2015) - Usluoğullari, Betül; Kaygusuz, Ikbal; Simavli, Serap; Eser, Ayla; Inegol Gumus, İknur
Abstract: Mean platelet volume (MPV) is a risk factor for cardiovascular complications, cerebrovascular disorders, and low-grade inflammatory conditions prone to arterial and venous thromboses. Cesarean delivery is the most important risk factor for pulmonary embolism, stroke, and intracranial venous thrombosis. The hypothesis is that increase in the prevalence of cesarean section and high MPV may be associated with cardiovascular complications such as stroke along with intracranial complications in addition to known systemic and surgical complications. In this study, platelet counts and MPV for postpartum women who delivered by cesarean section and normal vaginal parturition are compared. The subjects were divided in two groups, one was study group consisting of 118 patients giving birth by cesarean section and the other was the control group consisting 94 patients giving birth by normal vaginal parturition. Peripheral venous blood samples in EDTA tubes were collected from all the subjects 1 week before and after the delivery for their prenatal and postpartum periods, respectively. The values were compared between the groups and also before and after the delivery. In the cesarean group, while the MPV level was 8.60 (1.64) fl in the prenatal period, it increased to 9.10 (2.00) fl in the postnatal period ( p < 0.001). Group effect, time effect (independent from group effect), and group*time interaction effect were statistically significant for MPV variable ( p = 0.032, p < 0.001, and p = 0.012, respectively). This study concluded that MPV, along with several other factors, may be used as a prognostic, independent, and therapeutic marker in patients who are inclined to thrombotic events after cesarean section.